A preliminary investigation of the flow over a particular wing body combination at Mach number 2 - Busing, J. R.; Lilley, G. M. (College of Aeronautics, 1955)
Results are presented of visual tests, by surface flow and Schlieren techniques, of the flaw over a particular wing body combination at M = 2.0, made in the 9in x 9in supersonic wind tunnel at the College of Aeronautics. It should be noted that the photographs in this report represent only a small part of all the data collected. The effects of providing roughened bands and air jets for transition fixation on the body are discussed. It is shown that although such methods may be satisfactory at zero or low angles of incidence they do not fix transition uniformly over the complete body circumference at higher incidences. For this reason the main part of the tests have been performed with free transition. The formation of vortex sheets on both wings and body is discussed for a range of incidence and roll angles and some conclusions are drawn as to the shape of the vortex pattern and its induced flow effects.